MODERATING EFFECT OF BANK SIZE ON THE RELATIONSHIP BETWEEN INTEREST RATE, LIQUIDITY, AND PROFITABILITY OF COMMERCIAL BANKS IN NIGERIA - Shehu Usman Hassan; Bello Sabo; Ismai'l Idris Tijjani; Idris Ahmed Aliyu (Gusau Journal of Accounting and Finance, 2023)
The recurring instability of commercial banks’ performance in Nigeria have triggered stakeholders to deploy efforts toward providing solutions where the desired result is yet to be achieved. Consequently, this study examined the moderating effect of bank size on the relationship between interest rate, liquidity, and performance of the banks in Nigeria. An ex-post-facto research design was adopted, where the bank-specific data were sourced from the published annual financial statements of 12 commercial banks listed on the Nigerian Stock Exchange and the macroeconomic data were extracted from the WDI database for a ten-firm-year period from 2011 to 2020. The analysis was done using the panel regression technique with the support of Stata software version 14.2. Findings on the direct effects showed a significant and negative relationship between deposit rate and performance, and both the lending rate and loan-to-deposit ratio have positive and significant relationships with performance. Meanwhile, the intervention effects showed that the bank size has positively moderated the relationship between deposit rate and performance; whereas bank size has negatively moderated the relationship between loan-to-deposit ratio and performance. Therefore, the study recommended that banks should grow their assets to enable them to achieve economies of scale and cost efficiency.